Writer’s cramp as a presentation of L-2-hydroxyglutaric aciduria - Termsarasab, Pichet (J Clin Mov Disord, 2014)
L-2-hydroxyglutaric aciduria (L2HGA) is a neurometabolic disorder characterized by macrocephaly, seizures, progressive mental retardation, pyramidal signs, ataxia and tremor. Dystonia is an under-recognized feature of this entity in the literature. We report two siblings with L2HGA, one of whom presented with writer’s cramp followed by dystonia of the other hand. An elevated plasma lysine, highly elevated urine 2-hydroxyglutaric acid, and MRI with characteristic findings (leukoencephalopathy of bilateral subcortical white matter sparing central white matter) suggested the diagnosis, which was confirmed by genetic testing. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40734-014-0009-9) contains supplementary material, which is available to authorized users.